2022
DOI: 10.1155/2022/8549532
|View full text |Cite
|
Sign up to set email alerts
|

Xeroderma Pigmentosum: A Genetic Condition Skin Cancer Correlated—A Systematic Review

Abstract: Background. Xeroderma pigmentosum (XP) is a rare autosomal recessive disorder of UV radiation-induced damage repair that is characterized by photosensitivity and a propensity for developing, among many others, skin cancers at an early age. This systematic review focused on the correlation between the clinical, pathological, and genetic aspects of XP and skin cancer. Methods. A systematic review was conducted through a literature search of online databases PubMed, Cochrane Library, SciELO, and Google Scholar. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 64 publications
0
14
0
Order By: Relevance
“…They found that the G allele of polymorphism rs1800975 is associated with an increased risk of BCC and SCC and the seven haplotypes were in the Hardy-Weinberg equilibrium. This was the first study to relate polymorphisms in the XPA gene with the predisposition to the development of non-melanoma skin cancer [15]. Differently from Miller et al [15], Ding et al performed a meta-analysis to analyze the association of rs1800975 polymorphism with cancer risk.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…They found that the G allele of polymorphism rs1800975 is associated with an increased risk of BCC and SCC and the seven haplotypes were in the Hardy-Weinberg equilibrium. This was the first study to relate polymorphisms in the XPA gene with the predisposition to the development of non-melanoma skin cancer [15]. Differently from Miller et al [15], Ding et al performed a meta-analysis to analyze the association of rs1800975 polymorphism with cancer risk.…”
Section: Resultsmentioning
confidence: 99%
“…This was the first study to relate polymorphisms in the XPA gene with the predisposition to the development of non-melanoma skin cancer [15]. Differently from Miller et al [15], Ding et al performed a meta-analysis to analyze the association of rs1800975 polymorphism with cancer risk. They verified that of the 36 control cases analyzed, in general there was no significant association between the polymorphism and the susceptibility to develop cancer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutations in specific NER genes cause the genetic syndrome xeroderma pigmentosum (XP), characterized by hypersensitivity to UV radiation, increased incidence of tumors in areas exposed to sunlight, and, in 20%-30% of the patients with XP, progressive neurodegeneration. [7][8][9][10][11][12] Photoproducts may persist in cells undergoing DNA replication even in NER-proficient cells. Therefore, CPDs may block replicative DNA polymerases, generating cellular stress and a fragile structure in the replication fork, 4,5,13 while 6-4PPs are usually repaired in a few hours.…”
Section: Introductionmentioning
confidence: 99%
“…Different mechanisms emerged during evolution to resolve these lesions, and the primary repair pathway in mammalian cells is nucleotide excision repair (NER). Mutations in specific NER genes cause the genetic syndrome xeroderma pigmentosum (XP), characterized by hypersensitivity to UV radiation, increased incidence of tumors in areas exposed to sunlight, and, in 20%–30% of the patients with XP, progressive neurodegeneration 7–12 …”
Section: Introductionmentioning
confidence: 99%